Lercanidipine in general practice settings: safety and effectiveness. The LAPSE Study results - N. R. Robles; J. A. Canelada; M. Iglesias; E. Angulo; A. López Acedo; E. Díaz Olea; F. Cidoncha; M. Guerras; J. Fuentes; J. Garrido; J. Lapie; J. Peña; et al. (Кардиоваскулярная терапия и профилактика)
Objective: To determine the safety and effectiveness of a calcium antagonist (CA) lercanidipine in the general practice settings. Material and methods: 110 patients with essential arterial hypertension (AH) were included in the study (mean age 62,3±10,8 years; 51 men, 53 women; 38% with obesity (O) and body mass index, BMI, >30 kg/m2; 10 with diabetes mellitus, DM). In total, 104 patients completed the follow-up protocol. All patients were treated with lercanidipine (10 mg once daily in the morning). General clinical, biochemical and instrumental examination was performed at each visit: at baseline, at Days 45, 90, and 180. When blood pressure (BP) was not controlled, a second antihypertensive drug was added (typically, antiadrenergic agents, but not CA), with additional examination in 30 days. If BP was not controlled by combined antihypertensive therapy, the patients were excluded from the follow-up. Results: Significant reductions in both systolic BP, SBP (baseline 157,4±11,7 vs. 131,1±6,8 mm Hg; p<0,001) and diastolic BP, DBP (baseline 94,7±5,8 vs. 80,0±5,5 mm Hg; p<0,001) were achieved. At the end of the study, mean SBP and DBP reductions were 26,7 and 15,6 mm Hg, respectively. In 84,3% of the patients, both SBP and DBP were controlled (<140/90 mm Hg). Thirty patients needed a second antihypertensive medication to control BP at the first visit, compared to 26 at the study end. The overall incidence of adverse effects was 4,4% (n=6). Only 3 patients withdrew from the treatment due to adverse effects. Plasma cholesterol (CH) level decreased from 225,3±41,0 to 216,7±25,3 mg/dl (p=0,03), and concentration of urates decreased from 5,6±1,6 to 5,1±1,4 mg/ dl (p=0,03). Conclusions: In general practice settings, a CA lercanidipine demonstrated high antihypertensive effectiveness and minimal incidence of adverse effects. An important aspect of its therapeutic potential is metabolic neutrality, confirmed by beneficial effects on plasma levels of CH and urates.